(untitled) (Bangladesh Heart Journal, 2018)
Objective: In this review, we assess the outcome of surgical revascularization technique, coronary artery bypass grafting (CABG) with or without coronary endarterectomy (CE) for patients with diffuse coronary artery disease in a single surgeon’s practice. Methods: We retrospectively reviewed 2189 patients who experienced OPCABG with or without CE between January 2009 and December 2016. The following variables were compared in this study- Intubation time, ICU stay, Postoperative MI, Arrhythmia, renal impairment, stroke and ICU mortality. Results: Of 2189 patients, 1000 patients required coronary endarterectomy in addition to OPCABG. Initially, there was a higher mortality rate and incidence of postoperative blood transfusion in the group of patients who had CE in addition to CABG, with no significant difference in other outcomes. But postoperative use of Heparin, Warfarin and Double antiplatelet agent was associated with decreased mortality significantly in our study. In comparison to other group, the patients in the combined CE with CABG group had a higher incidence of male sex, past MI, and poor left ventricular function. However,emergency CABG, renal impairment, poor left ventricular function, and also peripheral vascular disease were associated with higher mortality in both group of the patients; CE was not a predictor of postoperative mortality. Conclusions: Total surgical revascularization is attainable and accomplishes, when Coronary endarterectomy is performed in addition to Off-pump coronary artery bypass graft in patients when there is no other choice for satisfactory revascularization. Bangladesh Heart Journal 2017; 32(2) : 77-84